Prevalence of unplanned first pregnancy and socioeconomic factors in Benin: a cross-sectional and analytical study - Mahouli Mireille-Marie Mintogbe; Elihou Adje; Victorien Tamègnon Dougnon; Clément Ahoussinou; Mouftaou Amadou Sanni (BMJ Publishing Group, 2024)
Background Early or unplanned pregnancy is an obstacle to the well-being of adolescent girls, especially as early motherhood has health and social consequences on the young mother and the newborn. This also negatively impacts maternal and infant morbidity and mortality. The aim of this study is to determine the prevalence of unplanned first pregnancies and the explanatory factors among adolescent girls.Methods Data were collected from a sample of 738 adolescent girls aged 15-19 years in the 12 departments of Benin. Analyses focused on teenagers who were pregnant for the first time or had at least one child at the time of the survey (337 individuals). Descriptive and bivariate analyses and logistic regression were used.Results The prevalence of unplanned first pregnancies was 80.1% (n=270). The frequency of unplanned first pregnancies was higher among adolescents who had reached secondary school or higher (85.7%, p=0.027), those who had spent their socialisation period in big cities (88.5%, p=0.018) and those whose financial needs were not met (84.8%, p=0.014). The main explanatory factor identified was unmet financial needs. Indeed, adolescents with unmet financial needs were 1.7 times (p=0.041) more likely to have an unplanned first pregnancy than those whose needs were met.Conclusion Multisectoral interventions are needed to reduce the prevalence of unplanned first pregnancies, which can compromise adolescent girls' academic and career plans. These interventions could focus on sexual and reproductive health education, girl empowerment, improvement of households' socioeconomic conditions, etc.